The burden of chronic diseases and cost-of-care in subjects with HIV infection in a Health District of Northern Italy over a 12-year period compared to that of the general population. (December 2016) - Quiros-Roldan, Eugenia; Magoni, Michele; Raffetti, Elena; Donato, Francesco; Scarcella, Carmelo; Paraninfo, Giuseppe; Castelli, Francesco
Abstract Background The increase in life expectancy of HIV-infected patients has driven increased costs due to life-long HIV treatment and concurrent age-related comorbidities. This population-based study aimed to investigate the burden of chronic diseases and health costs for HIV+ subjects compared to the general population living in Brescia Local health Agency (LHA) over a 12-year period. Methods LHA database recorded diagnoses, deaths, drug prescriptions and health resource utilization for all residents during 2003–2014. We estimated HIV prevalence and incidence, HIV-related mortality as well as prevalence of chronic diseases in HIV+ subjects. Observed/expected ratio of chronic diseases was calculated by indirect standardization with the general population as reference. Direct cost of HIV care and determinants were estimates across the period. Results HIV prevalence increased from 220 to 307 per 100 000 person-years while incidence decreased from 16.1 to 10.8 per 100 000 person-years from 2003 to 2014. Prevalence of most comorbidities increased over time but it reduced significantly (annual mean change − 0.7 %) when adjusting for age and gender. Observed to expected ratio for each chronic disease in HIV+ subjects decreased over time. Cost of HIV+ cures increased (+25 %) mainly due to cost for drugs (+50 %) but it stabilized in recent years. CD4+ cell count at the time of diagnosis was an important predictor of cost for HIV management. Conclusions Expenditures for HIV-infection are driven mainly by drugs cost and they have increased overtime. However, our findings suggest that spending on public health for HIV care can improve prognosis of HIV-infected patients, reduce transmission of HIV infection and reduce the global burden of chronic diseases, leading to a reduction of HIV global cost in the medium-long time.